Improving marine fisheries management in Southeast Asia: Results of a regional fisheries stakeholder analysis. (March 2016) - Pomeroy, Robert; Parks, John; Courtney, Kitty; Mattich, Nives
Abstract: A regional fisheries stakeholder assessment identified key regional issues and trends facing marine capture fisheries in Southeast Asia, as well as identifying relevant considerations and strategies in potentially addressing such regional issues and trends. The analysis provided a better understanding of the interplay between stakeholders;identifying key points of influence as well as strengths and weaknesses within the framework of promoting sustainable fisheries in a multistakeholder context. Several strategies are presented on how to address the priority issues and threats that face marine capture fisheries in the Southeast Asian region. Highlights: Many fisheries issues in Southeast Asia are transboundary. Improved management will involve regional dialogues and strategies. Develop and support regional alliances and networks. Governments need to partner with the private sector.